2001
DOI: 10.1590/s0103-90162001000200012
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade agrícola de cultivares de cana-de-açúcar em diferentes solos e épocas de colheita<A NAME="TOP1"></A>

Abstract: *Autor correspondente RESUMO: A cultura da cana-de-açúcar é destaque no cenário agrícola do Brasil, sendo cultivada em vários tipos de ambiente (associação de clima e solo). O estudo das respostas dos diferentes cultivares em cada ambiente de produção auxilia a maximizar a exploração econômica da cultura. Neste contexto, três experimentos em blocos completos casualizados com quatro repetições foram delineados para determinar as produtividades de colmos e a pol % cana de nove cultivares d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
47

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 2 publications
1
15
0
47
Order By: Relevance
“…Sugarcane has been cultivated in different types of soil under the influence of various abiotic factors that are peculiar to each region, evidencing different production levels (Maule et al, 2001). Among various abiotic factors, water deficiency must be highlighted, due to the harmful effects caused on plant development (Vitorello et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane has been cultivated in different types of soil under the influence of various abiotic factors that are peculiar to each region, evidencing different production levels (Maule et al, 2001). Among various abiotic factors, water deficiency must be highlighted, due to the harmful effects caused on plant development (Vitorello et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to minimize the use of mineral diesel oil and, thus, the emission of pollutants into the atmosphere are being made in many countries by replacing mineral diesel or by adding renewable fuels to the blend (MAULE et al, 2001). GRANDO (2005) proved the benefits of green fuels (biofuels), and showed that similar to biodiesel, ethanol can also contribute to improving environmental conditions by reducing gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…O nordeste brasileiro detém apenas 10,1% da produção nacional enquanto o estado do Ceará contribui com aproximadamente 0,03% da produção canavieira na região (Brasil, 2012). Esta baixa participação se deve principalmente às baixas e irregulares precipitações pluviométricas anuais registradas no nordeste, que se situam em torno de aproximadamente 750 mm, sendo esta média anual inferior às exigências hídricas da cana-de-açúcar que se concentra no intervalo compreendido entre 1.400 e 2.000 mm, como observado por pesquisadores (Sousa et al, 1999;Maule et al, 2001). Desta forma, a prática da irrigação se torna fundamental para a produção de cana-de-açúcar no Ceará.…”
Section: Introductionunclassified